(untitled) (Tribhuvan Journal, 2025)
The use of authentic materials has gained increasing attention in language pedagogy due to their potential to bridge the gap between classroom instruction and real-world language use. In ESL/EFL context, learners are exposed to prescribed textbook materials that can limit their communicative competence and intrinsic motivation. Against this background, this study explores the pedagogical role of authentic materials in enhancing learners’ motivation and facilitating meaningful language learning.The primary objective of the study is to examine how authentic materials influence learners’ motivational orientations and language learning experiences from a pedagogical perspective. To accomplish the objective, researcher adopted narrative research design under the qualitative research method. This research is completed through a narrative case analysis on the basis of unstructured interview making the meaning from informant’s (teacher) 15 years of teaching experiences who used authentic materials in classroom teaching. Researcher purposively selected an experienced teacher and focused on studying a single person, gathered data through the collection of stories; reporting individual experiences and discussing the meaning of those experiences. Discussing on narrative analysis, the findings indicate that authentic materials significantly enhance learners’ intrinsic motivation by increasing exposure to contextualized language, cultural relevance, and pragmatic usage. It revealed that there was greater interest, participation, and confidence in using English for communicative purposes while using authentic materials. It was acknowledged that authentic materials support learner autonomy and foster critical thinking.The study underscores the pedagogical significance of authentic materials as a motivational and instructional resource in language education. The findings offer practical implications for curriculum designers, teachers, and teacher educators seeking to promote communicative competence through authenticity driven pedagogy. It suggests that careful selection and pedagogical mediation of authentic materials can lead to more meaningful, motivating, and effective language learning experiences.